(untitled) (DAPesquisa, 2020)
The article proposes the analysis of aspects of the exhibition Les Immateriaux. Curated by the philosopher Jean-François Lyotard in 1964, it was presented at the Center Georges Pompidou, in Paris, from March 28 to July 15 of 1985. The exhibition marked a milestone in the history of the exhibitions for serving as a visual vehicle for the transmission of a philosophical discourse. It is understood that the relevance of the analysis comes from the possibility of discussing aspects of the methodology for studying the history of exhibitions, the use of curatorship combined with philosophical thinking and the diagnosis of characteristic aspects of contemporary curatorship.